DESIGN FEATURES OF AMERICAN AND BRITISH MUSIC POSTERS IN THE SECOND HALF OF THE 20TH – EARLY 21ST CENTURY - Колісник, О. В.; Приходько , І. В.; Сімак, А. І. (Art and Design, 2023)
The purpose of this work is to carry out a visual and stylistic analysis of music posters of the USA and Great Britain of the second half of the 20th – beginning of the 21st century and the design solutions used in their creation; тo investigate the specifics of advertising posters for musical events, to identify the peculiarities of their design and placement of characteristic elements depending on a certain musical genre. Methodology. A comprehensive approach to the study of music posters was used, which allowed to establish the features of their design and compositional solutions. The comparative analysis of advertising posters is carried out and the generalized characteristic of the design decisions connected with concrete musical genres is created. In the course of the research, scientific analysis of sources were used to identify the main trends of figurative expression in advertising. Results. The peculiarities of music posters on the example of advertising posters of world-famous performers from the USA and Great Britain of the second half of the XX century and the present are considered. Compositional techniques and tools used to implement various design solutions are analyzed. Specific techniques of graphic image and the main elements inherent in the posters of the music industry are identified. Scientific novelty. The peculiarities of the visual language of the music bill / poster of the second half of the 20th century and the present are revealed based on the study of the posters of music artists in the USA and Great Britain. The features of the classical poster are revealed, in what forms it exists and what design tools and artistic and aesthetic elements are characteristic of this or that musical style. The influence of artistic means of graphic design, photography and illustration on the design of posters is traced. A comparative analysis of the visual elements of posters depending on their musical genre was carried out. Practical significance. The materials of the work can be used in further research and classification of music posters. The analysis of the existing visual elements of the posters is carried out and their comparative characteristics are presented, which highlights the current trends in the creation of music posters.